Niobium oxide electrode performance boosted by molybdenum doping and calcination for supercapacitor applications - Al Mubarok, Muhammad Ramadhan; Nurfitria, Rima; Aflaha, Rizky; Nurfani, Eka; Rianjanu, Aditya (Green and Sustainable Materials Society, 2025)
Niobium pentoxide (Nb2O5) is a promising pseudocapacitive material for supercapacitor applications due to its high theoretical capacitance and electrochemical stability. However, its practical performance is limited by low electrical conductivity and poor ion transport kinetics. In this work, we report the enhancement of Nb2O5 electrode performance through molybdenum (Mo) doping and thermal calcination. Mo-doped Nb2O5 nanostructures were synthesized via a hydrothermal method followed by calcination at 500 °C. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) confirmed a rougher morphology and homogeneous Mo distribution in the doped sample. X-ray diffraction (XRD) revealed a structural transformation from a deformed orthorhombic phase in pristine Nb2O5 to a more crystalline pseudohexagonal phase in Mo-Nb2O5-500. Electrochemical analysis demonstrated a significant improvement in capacitive behavior, with Mo-Nb2O5-500 achieving a specific capacitance of 55.3 F/g at 5 mV/s, which is five times higher than the undoped sample. All electrodes exhibited stable cycling performance. These results highlight the synergistic role of Mo doping and calcination in enhancing the electrochemical properties of Nb2O5, offering a viable approach for developing high-performance pseudocapacitor electrodes.